TINJAUAN DAMPAK KREDIT BERMASALAH TERHADAP PROFITABILITAS PADA BANK KBMI III PERIODE 2020-2021 - Dinda Olivia Nur, (2022)
Banks in carrying out their activities during the Covid-19 pandemic caused several banks included in the Bank Group Based on Core Capital (KBMI) III to experience an increase in non-performing loans caused by the declining financial condition of the debtor's business activities so that they experienced an inability to pay their obligations to the bank. For this reason, banks must maintain their NPL level by making efforts to save credit through the 3Rs, namely rescheduling, reconditioning, and restructuring. According to Bank Indonesia Regulation Number 21/12/PBI/2019, a bank can be said to be healthy when the NPL level is below 5%. This writing aims to determine the impact of non performing loans on the level of profitability at the bank KBMI III. The data used is the annual report published through the website of each bank for the 2020-2021 period. Based on the results of this paper, it shows that there is an impact of non performing loans on profitability, the high level of lending activities carried out by banks, there is a risk of non-performing loans which will have an impact on profit (ROA).